The Validity of the ActiPed for Physical Activity Monitoring - Brown, D. K.; Grimwade, D.; Martinez-Bussion, D.; Taylor, M.J. D.; Gladwell, V. F. (International Journal of Sports Medicine, 2013)
The ActiPed (FitLinxx) is a uniaxial accelerometer, which objectively measures physical activity, uploads the data wirelessly to a website, allowing participants and researchers to view activity levels remotely. The aim was to validate ActiPed’s step count, distance travelled and activity time against direct observation. Further, to compare against pedometer (YAMAX), accelerometer (ActiGraph) and manufacturer’s guidelines. 22 participants, aged 28±7 years, undertook 4 protocols, including walking on different surfaces and incremental running protocol (from 2 mph to 8 mph). Bland-Altman plots allowed comparison of direct observation against ActiPed estimates. For step count, the ActiPed showed a low % bias in all protocols: walking on a treadmill ( − 1.30%), incremental treadmill protocol ( − 1.98%), walking over grass ( − 1.67%), and walking over concrete ( − 0.93%). When differentiating between walking and running step count the ActiPed showed a % bias of 4.10% and  − 6.30%, respectively. The ActiPed showed >95% accuracy for distance and duration estimations overall, although underestimated distance (p<0.01) for walking over grass and concrete. Overall, the ActiPed showed acceptable levels of accuracy comparable to previous validated pedometers and accelerometers. The accuracy combined with the simple and informative remote gathering of data, suggests that the ActiPed could be a useful tool in objective physical activity monitoring.
Keywords: accelerometer; motion sensor; accuracy; steps